If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1 = 5 + 2x Reorder the terms: -1 + 5x = 5 + 2x Solving -1 + 5x = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1 + 5x + -2x = 5 + 2x + -2x Combine like terms: 5x + -2x = 3x -1 + 3x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 -1 + 3x = 5 + 0 -1 + 3x = 5 Add '1' to each side of the equation. -1 + 1 + 3x = 5 + 1 Combine like terms: -1 + 1 = 0 0 + 3x = 5 + 1 3x = 5 + 1 Combine like terms: 5 + 1 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| 10v^2=-9 | | 5x(6y*4x)=65 | | (x)(2x)=28x | | 12+n=-17 | | -8-4(1+6f)=-33 | | 4x+1-(6)=3+2x | | 5(4)-10y=20 | | 2/-7/-4= | | 3x+7-2x-1=x+10 | | X-2+x-2=x+3 | | -2(4s-5)-10=-2(9s+8)-3 | | 5(3)-10y=20 | | 5x(x)+75+5=2x+52 | | (2x+2)(2x+2)=168 | | 17=3(a+3)-a | | 5(1)-10y=20 | | 28x^2-68x=48 | | 19(4c-1)-8=74c+19 | | 127+8d=19+20d | | 5(-1)-10y=20 | | 2b^2-14b=b-7 | | 0=9x^2+3x-2 | | x^3+-3x^2+-22x=-24 | | 2(3x+5)+22=-4(2x-15) | | 5(-2)-10y=20 | | (6y+7)-(6+5y)=9 | | Y=4-5(-1) | | 18(v+4)-2v=4(4v+1)-8 | | 2*20-3x= | | 4(-7k+5)=-2-6k | | -0.3x+9.86=-0.1x+6.86 | | 6+5m= |